2013
DOI: 10.1021/ac3037359
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing Lipid Bilayer Nanodiscs and Silicon Photonic Sensor Arrays for Multiplexed Protein–Lipid and Protein–Membrane Protein Interaction Screening

Abstract: Soluble proteins are key mediators of many biochemical signaling pathways via direct interaction with the lipid bilayer and via membrane-bound receptors. Components of the cell membrane are involved in many important biological processes, including viral infection, blood clotting, and signal transduction, and as such, they are common targets of therapeutic agents. Therefore, the development of analytical approaches to study interactions at the cell membrane is of critical importance. Herein, we integrate two k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 48 publications
0
43
0
Order By: Relevance
“…More recently, membrane nanodiscs as a model system for natural membranes were attached to silicon ring resonators. Specifically, nanodiscs containing the glycolipid receptor GM1 were immobilized to the sensor surface by direct physisorption to test its interaction with the B subunit of cholera toxin (CTB) [325]. Also more recently it was shown that a WGM glass microsphere can be coated by vesicle fusions from a solution of small unilamellar vesicles formed from 1,2-dipalmitoyl-sn-glycero-3-phoshphocholine and 1,2-dioleoyl-sn-glycero-3-phoshphocholine, and cholesterol [326].…”
Section: Sensingmentioning
confidence: 99%
“…More recently, membrane nanodiscs as a model system for natural membranes were attached to silicon ring resonators. Specifically, nanodiscs containing the glycolipid receptor GM1 were immobilized to the sensor surface by direct physisorption to test its interaction with the B subunit of cholera toxin (CTB) [325]. Also more recently it was shown that a WGM glass microsphere can be coated by vesicle fusions from a solution of small unilamellar vesicles formed from 1,2-dipalmitoyl-sn-glycero-3-phoshphocholine and 1,2-dioleoyl-sn-glycero-3-phoshphocholine, and cholesterol [326].…”
Section: Sensingmentioning
confidence: 99%
“…In this regard, future modifications of the SMA copolymer (size, pendant group stoichiometry and functionalization with molecular tags) will likely be useful in the development of novel experimental applications. In addition to their utility in basic research, these nanoscale bilayers have vast potential for applied technologies, including the development of biocompatible systems for hydrophobic drug delivery and diagnostic applications (Murakami, 2012;Ng, Lovell, Vedadi, Hajian, & Zheng, 2013;Numata et al, 2013), nanoelectronic devices (Goldsmith et al, 2011;Ham et al, 2010), and multiplexed sensor arrays to detect protein interactions (Sloan, Marty, Sligar, & Bailey, 2013). Given the commercial availability of all components required for the synthesis of nanodiscs and SMAPLs/Lipodisqs®, we are sure to see these systems applied to an ever-expanding repertoire of MPs by many independent groups in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…(d) The phospholipid composition can be tailored to control physisorption efficiency and modulate protein interactions. Adapted with permission from [44]. Copyright (2013) American Chemical Society.…”
Section: Highlightsmentioning
confidence: 99%
“…The refractive index-based transduction methodology and multiplexing capability of microring resonators also make them highly promising to biomolecular screening and affinity characterization applications [22,31,42-44]. In contrast to endpoint-based methods, which only provide the thermodynamic binding constant, real-time monitoring technologies provide direct access to the kinetic rate constants that govern biomolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation